The Resilience of Sharia Insurance in MENA During the COVID-19 Pandemic: An Analysis of Financial Performance - Miranti, Titis; Meylianingrum, Kurniawati (Economica: Jurnal Ekonomi Islam, 2023)
The COVID-19 pandemic affects financial institutions worldwide, including Islamic financial institutions such as sharia insurance. This research focuses on sharia insurance in the Middle East and North Africa (MENA) that provide governance mechanisms and audit quality. The value of sharia insurance income in the MENA did not show a certain trend during the study period, although there were some extreme values during this COVID-19 pandemic. This study aims to examine the effect of the COVID-19 pandemic on sharia insurance earned in MENA. The quarterly data from 2010 to 2020 is used with panel regression as an analytical tool. As a result, the COVID-19 pandemic had no significant effect on sharia insurance earned in MENA. On the other hand, net income, long-term investment, assets have a significant effect. It shows that most sharia insurance in the MENA can survive during the COVID-19 pandemic. This study also confirms that Islamic financial institutions are still the best in their ability to stay during the COVID-19 pandemic. Moreover, sharia insurance is an alternative for welfare protection for residents in the MENA.